EFFECT OF ROOTS LICORICE EXTRACT AND SUCROSE ON VASE LIFE AND SOME CHARACTERISTIC CHIMICALS OF Dendranthema grandiflorum FLOWER - Khetam Rashed (Mesopotamia Journal of Agriculture, 2019)
This study was conducted in the physiology lab of the Department of Horticulture / Faculty of Agriculture / University of Dohuk during the period from 3rd of November 2009 to 20th of March 2010 to test the effects of preservation the flowers of extract of liquorice root at (0، 2.5، 5 g.l-1) and with sucrose at (0، 0.5، 1 g.l-1) on vase life، and some characteristic chemicals Dendranthema grandiflorum flower. Results showed that the highest increasing percentage founded at 1g.l-1 sucrose reached 1.63%, 10.15%, 9.18%, 5.66 %, 2.49%, 2.84%, 1.99%, 2.58% and 11.94 day for nitrogen percentage، protein percentage، carbohydrate percentage، C/N ratio، α- carotene، β – carotene، Astaxanthin، zeaxanthin and vase life، also the extract of liquorice root caused significantly increase on nitrogen percentage، protein percentage، carbohydrate percentage، C/N ratio- β carotene، α - carotene، Astaxanthin zeaxanthin and vase life، compared with non treated flowers the highest increasing where founded with high level 5g.l-1، all interactions between factors had significantly effect on all characters where studies.